Exploring extracellular vesicles in zoonotic helminth biology: implications for diagnosis, therapeutic and delivery - Qadeer, Abdul; Wajid, Abdul; Rafey, Hafiz Abdul; Nawaz, Saqib; Khan, Sawar; Rahman, Sajid Ur; Alzahrani, Khalid J.; Khan, Muhammad Zahoor; Alsabi, Mohammad Nafi Solaiman; Ullah, Hanif; Safi, Sher Zaman; Xia, Zanxian; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Extracellular vesicles (EVs) have emerged as key intercellular communication and pathogenesis mediators. Parasitic organisms’ helminths, cause widespread infections with significant health impacts worldwide. Recent research has shed light on the role of EVs in the lifecycle, immune evasion, and disease progression of these parasitic organisms. These tiny membrane-bound organelles including microvesicles and exosomes, facilitate the transfer of proteins, lipids, mRNAs, and microRNAs between cells. EVs have been isolated from various bodily fluids, offering a potential diagnostic and therapeutic avenue for combating infectious agents. According to recent research, EVs from helminths hold great promise in the diagnosis of parasitic infections due to their specificity, early detection capabilities, accessibility, and the potential for staging and monitoring infections, promote intercellular communication, and are a viable therapeutic tool for the treatment of infectious agents. Exploring host-parasite interactions has identified promising new targets for diagnostic, therapy, and vaccine development against helminths. This literature review delves into EVS’s origin, nature, biogenesis, and composition in these parasitic organisms. It also highlights the proteins and miRNAs involved in EV release, providing a comprehensive summary of the latest findings on the significance of EVs in the biology of helminths, promising targets for therapeutic and diagnostic biomarkers.